PENERAPAN METODE STORY TELLING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI "CERITA RAKYAT" di MI DARUL ULUM PASINAN BAURENO - Siti Khoirun Nisa'; Dwi Niswatul Fithriyah; Ira Rahmawati; Nur Lina Sufiyatin; Ilma Alfiyanti; Septia Relan Alivia Nanda Baisiroh (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the effectiveness of the storytelling method in improving student learning outcomes in folklore material at MI Darul Ulum Pasinan Baureno. The background of this study is the low interest and understanding of students due to monotonous learning. The storytelling method was chosen because it is able to present a fun, interactive, and meaningful learning atmosphere. With a qualitative approach, data were obtained through observation and testing. The results showed that storytelling increased students' interest, understanding, and ability in listening and retelling the contents of the story. Student learning outcomes also increased significantly. Storytelling also instills character values contained in folklore. In conclusion, storytelling is effectively applied in Indonesian language learning at the madrasah level.